Carbon-supported ternary metal ordered alloy nano material as well as preparation method and application thereof
By forming a carbon carbon -load metal orderly alloy nanomal material on the carbon carrier, the problem of reduced activity and stability of precious metal alloy catalysts under acidic conditions is solved, and the effect of improved catalytic activity and extension of service life.
Patent Information
- Application Number
- CN202411509540.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-28
AI Technical Summary
The existing noble metal alloy catalysts quickly dissolve transition metal atoms under acidic conditions, resulting in rapid reduction of catalytic activity and poor stability. A single transition metal cannot regulate the platinum electronic structure to achieve the optimal oxygen intermediate binding energy.
The carbon -loaded metal orderly alloy nanomical material is used to form an orderly ternary metal structure by loading valuable metals, transition metals and rare earth metals on the carbon carrier, and the electronic structure of rare earth metals regulates precious metals.
It improves the catalytic reaction catalytic activity of the catalyst, slows the rate of loss of transition metal, enhances the thermodynamic stability of the alloy structure, and prolongs the service life of the catalyst.
Smart Images

Figure CN119368722A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of alloy materials, and in particular relates to a carbon-supported ternary metal ordered alloy nanomaterial and a preparation method and application thereof. Background Art
[0002] Platinum-based alloy materials (mainly alloys formed with transition metals M: Cu, Fe, Ni, Co, etc.) have changed the electronic structure of platinum due to the "ligand effect", "strain effect", "geometric effect", etc. caused by the introduction of transition metals, weakening the binding energy between platinum surface atoms and oxygen-containing species, and improving the catalytic activity and stability of the catalyst in oxygen reduction reactions (Angewandte Chemie International Edition, 59 (2020) 18334-18348). Usually, due to the diffusion barrier of metal atoms in the bulk phase, metal alloys generally present a disordered solid solution structure. For example, platinum-cobalt alloy materials, in which platinum and cobalt atoms randomly occupy face-centered cubic positions. Under acidic conditions, the transition metal atoms on the surface of the disordered PtM alloy catalyst will quickly dissolve into the electrolyte, leaving a low-coordinated platinum surface, resulting in a rapid decrease in catalytic activity and poor stability (Nano Letters, 24 (2024) 3213-3220). An ordered alloy is a special structural alloy with a fixed stoichiometric ratio and a highly ordered atomic structure, in which each atom is in a regular and orderly fixed position, exhibiting a higher mixing enthalpy, which can slow down the dissolution of the transition metal M, thereby improving the structural stability of the alloy material (Nature Materials, 12 (2013) 81-87, Small18 (2022) 2202916).
[0003] However, in thermodynamics, although the ordered structure is a stable phase compared to the traditional disordered solid solution alloy structure, the transition metal will still gradually disappear, resulting in changes in the ordered alloy structure, and the activity and stability of the catalyst face serious problems (Nature Chemistry, 6 (2014) 732-738). In addition, the regulation of the electronic structure of platinum by a single transition metal still does not reach the optimal value of the oxygen intermediate binding energy.
[0004] Therefore, the technical issues of how to further regulate the electronic structure of precious metals, enhance their intrinsic catalytic ability, slow down the loss of transition metals, maintain a stable alloy structure, and extend the service life of alloy catalysts remain to be solved. Summary of the invention
[0005] The purpose of the present invention is to provide a carbon-supported ternary metal ordered alloy nanomaterial and its preparation method and application, so as to enhance the intrinsic catalytic ability of precious metals / transition metals, maintain a stable alloy structure, and extend the service life of the alloy catalyst.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] The present invention provides a carbon-supported ternary metal ordered alloy nanomaterial, comprising a carbon support and ternary metal ordered alloy nanoparticles supported on the surface of the carbon support or in the pore structure;
[0008] The ternary metal ordered alloy nanoparticles include noble metals, transition metals and rare earth metals, and the three metal atoms are arranged in order.
[0009] Furthermore, the particle size of the ternary metal ordered alloy nanoparticles is 1-50 nm, preferably 3-10 nm, and more preferably 3-5 nm.
[0010] Furthermore, the ternary metal ordered alloy nanoparticles account for 0.1-70% of the total mass of the nanomaterial, preferably 15-70%.
[0011] Furthermore, the ratio of the molar number of the noble metal to the sum of the molar numbers of the transition metal and the rare earth metal is selected from one of 1:1, 3:1 and 1:3.
[0012] Furthermore, the ratio of the molar number of the rare earth metal to the molar number of the transition metal is (0.01-1):1, preferably (0.01-1):1.
[0013] Furthermore, the carbon carrier includes one of natural carbon materials, artificial carbon materials or derived carbon materials, preferably conductive carbon black.
[0014] Furthermore, the precious metal includes one or more of platinum, palladium, ruthenium, iridium, gold, rhodium, osmium or silver.
[0015] Furthermore, the transition metal includes one or more of iron, cobalt, nickel, copper, zinc, manganese, molybdenum, tungsten, chromium, tin, lead or bismuth.
[0016] Furthermore, the rare earth metal includes one or more of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, scandium and yttrium.
[0017] The present invention also provides a method for preparing a carbon-supported ternary metal ordered alloy nanomaterial, comprising the following steps:
[0018] The carbon carrier, the noble metal precursor, the transition metal salt precursor, the rare earth metal salt precursor and the nitrogen-containing precursor are uniformly mixed and then calcined to obtain the carbon-supported ternary metal ordered alloy nanomaterial.
[0019] Furthermore, the noble metal precursor includes one or more of noble metal acid, chloride or nitrate.
[0020] Furthermore, the transition metal salt precursor includes one or more of nitrate, chloride, acetate or sulfate.
[0021] Furthermore, the rare earth metal salt precursor includes one or more of nitrate, chloride, acetate or sulfate.
[0022] Furthermore, the nitrogen-containing precursor includes one or more of polypyrrole, polyaniline, polythiophene, polydopamine, pyrrole, aniline, pyridine, polypyridine, ethylenediamine, triethylenetetramine, porphyrin, phthalocyanine, o-phenanthroline, imidazole, dopamine, thiophene, cyanamide, dicyandiamide, urea or melamine.
[0023] Furthermore, the specific mixing method includes one or more of grinding mixing, impregnation, ultrasonic mixing and rotary evaporation.
[0024] Furthermore, the solvents used in the immersion method, ultrasonic mixing method and rotary evaporation method include one or more of water, ethanol, methanol, acetone, ethylene glycol or isopropanol.
[0025] Furthermore, the calcination temperature is 500-1200°C.
[0026] Furthermore, the calcination time is 0.5-48h.
[0027] Furthermore, the calcination is carried out in a specific atmosphere.
[0028] Furthermore, the specific atmosphere includes one of argon, nitrogen, helium, hydrogen-nitrogen mixture, hydrogen-argon mixture, hydrogen-helium mixture, carbon monoxide-nitrogen mixture, carbon monoxide-argon mixture, carbon monoxide-helium mixture, hydrogen or carbon monoxide.
[0029] Furthermore, the volume concentration of the hydrogen or carbon monoxide in the mixed gas is 0.1-30%.
[0030] Furthermore, the cooling to room temperature after calcination includes one of natural cooling, rapid cooling and programmed cooling.
[0031] Furthermore, the programmed cooling has a cooling rate of 0.5-20°C / min.
[0032] The present invention also provides an application of a carbon-supported ternary metal ordered alloy nanomaterial, wherein the carbon-supported ternary metal ordered alloy nanomaterial is used to catalyze one or more of an oxygen reduction reaction, a hydrogen oxidation reaction, a hydrogen evolution reaction or an alcohol oxidation reaction.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] (1) The carbon-supported ternary metal ordered alloy nanomaterial prepared by the present invention forms an ordered alloy structure by introducing rare earth metals, and the electronic structure of the noble metal is regulated by the rare earth metals, thereby improving its catalytic activity.
[0035] (2) By introducing rare earth metals into the carbon-supported ternary metal ordered alloy nanomaterials prepared by the present invention, the loss rate of transition metals can be slowed down, thereby improving the thermodynamic stability of the alloy structure and extending the service life of the alloy material.
[0036] (3) The carbon carrier, precious metal, transition metal, and rare earth metal of the present invention have a wide range of choices and can be flexibly selected and adjusted according to actual production conditions and application requirements.
[0037] (4) The preparation method of the carbon-supported ternary metal ordered alloy nanomaterial of the present invention is simple, and suitable process conditions can be selected for the mixing, calcination, cooling and other processes to achieve the best preparation effect, which has good practical production value. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is the XRD diagram of the Pt2CoLa / C ordered alloy material prepared in Example 1.
[0039] Figure 2 This is the TEM image of the Pt2CoLa / C ordered alloy material prepared in Example 1.
[0040] Figure 3 It is a schematic diagram of the structure of the Pt2CoLa / C ordered alloy material prepared in Example 1.
[0041] Figure 4 This is the XRD diagram of the Pt / C material prepared in Comparative Example 1.
[0042] Figure 5 This is the XRD diagram of the PtCo / C alloy material prepared in Comparative Example 2.
[0043] Figure 6 This is the XRD diagram of the PtLa / C alloy material prepared in Comparative Example 3.
[0044] Figure 7 This is the polarization curve of the oxygen reduction reaction of the Pt2CoLa / C ordered alloy material prepared in Example 1.
[0045] Figure 8 This is the polarization curve of the oxygen reduction reaction of the Pt / C material prepared in Example 1.
[0046] Fig. 9 This is a polarization curve diagram of the oxygen reduction reaction of the PtCo / C alloy material prepared in Example 2.
[0047] Fig.10 This is the polarization curve of the oxygen reduction reaction of the Pt5La / C alloy material prepared in Example 3. DETAILED DESCRIPTION
[0048] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0049] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art. Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0050] Embodiment 1:
[0051] This embodiment provides a carbon-supported ternary metal ordered alloy nanomaterial, wherein the noble metal is platinum (Pt), the transition metal is cobalt (Co), the rare earth metal is lanthanum (La), and the carbon carrier is conductive carbon black (specific model is Ketjenblack EC-600JD). The specific preparation method of this embodiment is as follows:
[0052] Take 0.05g Ketjenblack EC-600JD in a 20ml sample bottle, add 0.0058g cobalt nitrate hexahydrate (Co(NO3)2·6H2O), 0.0207g chloroplatinic acid hexahydrate (H2PtCl6·6H2O), 0.0087g lanthanum nitrate hexahydrate (La(NO3)3·6H2O) and 0.3g cyanamide in anhydrous ethanol solution, ultrasonicate for 2h, and place the obtained viscous sample in a vacuum oven at 70℃ for 12h. The obtained solid powder is placed in an agate mortar and ground into powder, then moved to a tube furnace, calcined at 900℃ for 7h in a hydrogen-argon mixed gas (5% H2 / 95% Ar) atmosphere, and the heating rate is 10℃ / min. When the temperature naturally drops to room temperature, the obtained solid powder is Pt2CoLa / C ordered alloy material.
[0053] In the Pt2CoLa / C ordered alloy material prepared in this embodiment, the Pt2CoLa alloy nanoparticles account for 19% of the total mass. The ratio of the molar number of the noble metal to the sum of the molar number of the transition metal and the rare earth metal is 1:1, and the ratio of the molar number of the rare earth metal to the molar number of the transition metal is 1:1.
[0054] Figure 1 This is the XRD spectrum of the Pt2CoLa / C ordered alloy material prepared in this example. It can be seen from the figure that superlattice diffraction peaks corresponding to the PtCo ordered alloy appear at 24.0° and 33.2°. Figure 2This is the TEM image of the prepared Pt2CoLa / C ordered alloy nanomaterial. It can be seen from the figure that the size of the prepared alloy nanoparticles is about 3-5nm, and the ordered alloy nanoparticles are uniformly loaded in the pores of the carbon material. Figure 3 Schematic diagram of the structure of Pt2CoLa / C ordered alloy material. In the Pt2CoLa / C ordered alloy nanoparticles in the figure, blue represents platinum atoms, purple represents lanthanum atoms, and yellow represents cobalt atoms. It can be seen from the figure that platinum, lanthanum and cobalt atoms have fixed positions and present an ordered structure. The above results show that the ordered Pt2CoLa / C ordered alloy material was successfully prepared in this embodiment.
[0055] Embodiment 2:
[0056] This embodiment provides a carbon-supported ternary metal ordered alloy nanomaterial, wherein the noble metal is platinum (Pt), the transition metal is iron (Fe), the rare earth metal is lanthanum (La), and the carbon carrier is conductive carbon black (specific model is Ketjenblack EC-300JD). The specific preparation method of this embodiment is as follows:
[0057] Take 0.05g Ketjenblack EC-300JD and put it in a mortar. Then add 0.0081g iron nitrate nonahydrate (Fe(NO3)3·9H2O), 0.0207g chloroplatinic acid hexahydrate (H2PtCl6·6H2O), 0.0087g lanthanum nitrate hexahydrate (La(NO3)3·6H2O) and 0.3g cyanamide and other solids to the above carbon material, grind for 30min to obtain a mixed powder. The obtained solid mixed powder is moved to a tube furnace and calcined at 1000℃ for 5h under a hydrogen atmosphere at a heating rate of 10℃ / min. When the temperature naturally drops to room temperature, the obtained solid powder is a Pt2FeLa / C ordered alloy material.
[0058] In the Pt2FeLa / C ordered alloy material prepared in this embodiment, the Pt2FeLa alloy nanoparticles account for 18.96% of the total mass. The ratio of the molar number of the noble metal to the sum of the molar number of the transition metal and the rare earth metal is 1:1, and the ratio of the molar number of the rare earth metal to the molar number of the transition metal is 1:1.
[0059] Embodiment 3:
[0060] This embodiment provides a carbon-supported ternary metal ordered alloy nanomaterial, wherein the noble metal is platinum (Pt), the transition metal is cobalt (Co), the rare earth metal is lanthanum (La), and the carbon carrier is conductive carbon black (specific model is Vulcan XC-72). The specific preparation method of this embodiment is as follows:
[0061] 0.05g of Vulcan XC-72 was placed in a beaker containing 100ml of deionized water and ultrasonically treated for 30 minutes. Then, 0.0058g of cobalt nitrate hexahydrate (Co(NO3)2·6H2O), 0.0207g of chloroplatinic acid hexahydrate (H2PtCl6·6H2O), 0.0087g of lanthanum nitrate hexahydrate (La(NO3)3·6H2O) and 0.3g of urea and other solids were added to the above beaker and stirred for 30 minutes. Then, the solvent was evaporated by rotary evaporation to obtain a dry solid powder. The obtained solid mixed powder was moved to a tube furnace and calcined at 1200°C for 24h in a carbon monoxide / nitrogen atmosphere (containing 10% carbon monoxide) at a heating rate of 10°C / min. Then, the temperature was cooled to room temperature at a cooling rate of 2°C / min. The obtained solid powder was a Pt2CoLa / C ordered alloy material.
[0062] In the Pt2CoLa / C ordered alloy material prepared in this embodiment, the Pt2CoLa alloy nanoparticles account for 19% of the total mass. The ratio of the molar number of the noble metal to the sum of the molar number of the transition metal and the rare earth metal is 1:1, and the ratio of the molar number of the rare earth metal to the molar number of the transition metal is 1:1.
[0063] Embodiment 4:
[0064] This embodiment provides a carbon-supported ternary metal ordered alloy nanomaterial, wherein the noble metal is palladium (Pd), the transition metal is cobalt (Co), the rare earth metal is yttrium (Y), and the carbon carrier is conductive carbon black (specific model is Ketjenblack EC-600JD). The specific preparation method of this embodiment is as follows:
[0065] Take 0.05g Ketjenblack EC-600JD in a 20ml sample bottle, add 0.0058g cobalt nitrate hexahydrate (Ni(NO3)2·6H2O), 0.0071g palladium chloride (PdCl2), 0.0055g yttrium nitrate (Y(NO3)3) and 0.3g cyanamide in 1.6mL of anhydrous ethanol solution, ultrasonicate for 2h, and place the obtained viscous sample in a vacuum oven at 70℃ for 12h. The obtained solid powder is placed in an agate mortar and ground into powder, then moved to a tube furnace, and calcined at 1000℃ for 36h in a hydrogen-argon mixed gas (5% H2 / 95% Ar) atmosphere, with a heating rate of 10℃ / min. When the temperature naturally drops to room temperature, the obtained solid powder is a Pd2CoY / C ordered alloy material.
[0066] In the Pd2CoY / C ordered alloy material prepared in this embodiment, Pd2CoY alloy nanoparticles account for 12.61% of the total mass. The ratio of the molar number of the noble metal to the sum of the molar number of the transition metal and the rare earth metal is 1:1, and the ratio of the molar number of the rare earth metal to the molar number of the transition metal is 1:1.
[0067] Embodiment 5:
[0068] This embodiment provides a carbon-supported ternary metal ordered alloy nanomaterial, wherein the noble metal is platinum (Pt), the transition metal is cobalt (Co), the rare earth metal is lanthanum (La), and the carbon carrier is conductive carbon black (specific model is Ketjenblack EC-600JD). The specific preparation method of this embodiment is as follows:
[0069] Take 0.05g Ketjenblack EC-600JD and put it in a mortar, add 0.051g cobalt nitrate hexahydrate (Co(NO3)2·6H2O), 0.181g chloroplatinic acid hexahydrate (H2PtCl6·6H2O), 0.075g lanthanum nitrate hexahydrate (La(NO3)3·6H2O) and 1g cyanamide and other solids to the above carbon, grind for 30 minutes to obtain a mixed powder. The obtained solid mixed powder is moved to a tube furnace and calcined at 900℃ for 5h under hydrogen atmosphere at a heating rate of 10℃ / min. When the temperature naturally drops to room temperature, the obtained solid powder is Pt2CoLa / C ordered alloy material.
[0070] In the Pt2CoLa / C ordered alloy material prepared in this embodiment, the Pt2CoLa alloy nanoparticles account for 67.3% of the total mass. The ratio of the molar number of the noble metal to the sum of the molar number of the transition metal and the rare earth metal is 1:1, and the ratio of the molar number of the rare earth metal to the molar number of the transition metal is 1:1.
[0071] Embodiment 6:
[0072] This embodiment provides a carbon-supported ternary metal ordered alloy nanomaterial, wherein the noble metal is platinum (Pt), the transition metal is cobalt (Co), the rare earth metal is lanthanum (La), and the carbon carrier is conductive carbon black (specific model is Ketjenblack EC-600JD). The specific preparation method of this embodiment is as follows:
[0073] Take 0.05g Ketjenblack EC-600JD in a 20ml sample bottle, add 0.0047g cobalt nitrate hexahydrate (Co(NO3)2·6H2O), 0.031g chloroplatinic acid hexahydrate (H2PtCl6·6H2O), 0.0017g lanthanum nitrate hexahydrate (La(NO3)3·6H2O) and 0.1g cyanamide in 1.6mL of anhydrous ethanol solution, ultrasonicate for 2h, and place the obtained viscous sample in a vacuum oven at 70℃ for 12h. The obtained solid powder is placed in an agate mortar and ground into powder, then moved to a tube furnace and calcined at 900℃ for 7h in a hydrogen-argon mixed gas (5% H2 / 95% Ar) atmosphere with a heating rate of 10℃ / min. When the temperature naturally drops to room temperature, the obtained solid powder is Pt15 Co4La / C ordered alloy materials.
[0074] In this example, the Pt 15 In Co4La / C ordered alloy materials, Pt 15 The Co4La / C alloy nanoparticles account for 20.89% of the total mass. The ratio of the molar number of the noble metal to the sum of the molar number of the transition metal and the rare earth metal is 3:1, and the ratio of the molar number of the rare earth metal to the molar number of the transition metal is 0.25:1.
[0075] Embodiment 7:
[0076] This embodiment provides a carbon-supported ternary metal ordered alloy nanomaterial, wherein the noble metal is platinum (Pt), the transition metal is cobalt (Co), the rare earth metal is lanthanum (La), and the carbon carrier is conductive carbon black (specific model is Ketjenblack EC-600JD). The specific preparation method of this embodiment is as follows:
[0077] Take 0.05g Ketjenblack EC-600JD in a 20ml sample bottle, add 0.0116g cobalt nitrate hexahydrate (Co(NO3)2·6H2O), 0.0104g chloroplatinic acid hexahydrate (H2PtCl6·6H2O), 0.0087g lanthanum nitrate hexahydrate (La(NO3)3·6H2O) and 0.1g cyanamide dissolved in 1.6mL of anhydrous ethanol solution, ultrasonicate for 2h, and place the obtained viscous sample in a vacuum oven at 70℃ for 12h. The obtained solid powder is placed in an agate mortar and ground into powder, then moved to a tube furnace, calcined at 900℃ for 5h in a hydrogen-argon mixed gas (5% H2 / 95% Ar) atmosphere, and the heating rate is 10℃ / min. When the temperature naturally drops to room temperature, the obtained solid powder is a PtCo2La / C ordered alloy material.
[0078] In the PtCo2La / C ordered alloy material prepared in this embodiment, PtCo2La alloy nanoparticles account for 15.31% of the total mass. The ratio of the molar number of noble metal to the sum of the molar number of transition metal and rare earth metal is 1:3, and the ratio of the molar number of rare earth metal to the molar number of transition metal is 0.5:1.
[0079] Comparative Example 1:
[0080] This comparative example provides a carbon-supported precious metal material, specifically a Pt / C material, and the preparation method is as follows:
[0081] Take 0.05g Ketjenblack EC-600JD in a 20ml sample bottle, add 1.6mL of anhydrous ethanol solution containing 0.0207g hexahydrate chloroplatinic acid (H2PtCl6·6H2O) and 0.3g cyanamide, and ultrasonicate for 2h. The viscous sample is placed in a vacuum oven at 70℃ and dried for 12h. The solid powder is placed in an agate mortar and ground into powder, then moved to a tube furnace and calcined at 900℃ for 7h in a hydrogen-argon mixed gas (5% H2 / 95% Ar) atmosphere with a heating rate of 10℃ / min. When the temperature naturally drops to room temperature, the solid powder obtained is Pt / C material.
[0082] Figure 4 This is the XRD diagram of the Pt / C material prepared in this comparative example. It can be seen from the figure that all diffraction peaks can correspond to the standard spectrum of elemental platinum, which indicates that the Pt / C nanomaterial is successfully prepared.
[0083] Comparative Example 2:
[0084] This comparative example provides a carbon-supported noble metal-transition metal alloy nanomaterial, specifically PtCo / C, and the preparation method is as follows:
[0085] Take 0.05g Ketjenblack EC-600JD in a 20ml sample bottle, add 0.0116g cobalt nitrate hexahydrate (Co(NO3)2·6H2O), 0.0207g chloroplatinic acid hexahydrate (H2PtCl6·6H2O) and 0.3g cyanamide in 1.6mL of anhydrous ethanol solution, ultrasonicate for 2h, and place the obtained viscous sample in a vacuum oven at 70℃ for 12h. The obtained solid powder is placed in an agate mortar and ground into powder, then moved to a tube furnace, and calcined at 900℃ for 7h in a hydrogen-argon mixed gas (5% H2 / 95% Ar) atmosphere, with a heating rate of 10℃ / min. When the temperature naturally drops to room temperature, the obtained solid powder is a PtCo / C ordered alloy material.
[0086] Figure 5 The XRD diagram of the PtCo / C material prepared in this comparative example shows that the superlattice diffraction peaks corresponding to the PtCo ordered alloy appear at 23.8° and 33.2°, which indicates that the PtCo ordered alloy is successfully prepared.
[0087] Comparative Example 3:
[0088] This comparative example provides a carbon-supported precious metal-rare earth metal alloy nanomaterial, specifically Pt5La / C, and the preparation method is as follows:
[0089] Take 0.05g Ketjenblack EC-600JD in a 20ml sample bottle, add 1.6mL of anhydrous ethanol solution containing 0.0207g of chloroplatinic acid hexahydrate (H2PtCl6·6H2O), 0.0173g of lanthanum nitrate hexahydrate (La(NO3)3·6H2O) and 0.3g of cyanamide, and ultrasonicate for 2h. The viscous sample is placed in a vacuum oven at 70℃ and dried for 12h. The solid powder is placed in an agate mortar and ground into powder, then moved to a tube furnace and calcined at 900℃ for 7h in a hydrogen-argon mixed gas (5% H2 / 95% Ar) atmosphere at a heating rate of 10℃ / min. When the temperature naturally drops to room temperature, the solid powder obtained is a PtLa / C ordered alloy material. Figure 6 This is the XRD diagram of the PtLa / C material prepared in this comparative example. It can be seen from the figure that all diffraction peaks correspond to the Pt5La alloy, which indicates that the Pt5La / C alloy material is successfully prepared.
[0090] The present invention conducts the following tests on the carbon-supported metal materials obtained in Example 1 and Comparative Examples 1-3:
[0091] A three-electrode test system was used, the electrolyte was 0.1M HClO4, and the CHI-760E electrochemical station was used at room temperature. Platinum foil was used as the counter electrode and Ag / AgCl was used as the reference electrode. The catalyst slurry was prepared with ultrapure water and isopropanol (v / v=3:1) and a certain amount of 5wt% Nafion solution. 20μL of the catalyst slurry was placed on a glassy carbon electrode (d=5mm, with a geometric electrode area of 0.196cm 2 ) and dried in air to prepare the working electrode. The Pt loading of all samples was 20 μg cm -2 In a 0.1M HClO4 solution saturated with N2, the -1 The cyclic voltammetry curves were tested at a scan rate of 0.05 V to 1.05 V. The oxygen reduction polarization curves were carried out in an O2-saturated 0.1 M HClO4 solution at a scan rate of 10 mV s -1 The electrode rotation rate was 1600 rpm. Before recording the oxygen reduction polarization curve, the electrode was in an Ar-saturated 0.1 M HClO4 solution at 20 mV s -1 The activation of cyclic voltammetry curve was tested at a scan rate ranging from 0.05V to 1.05V.
[0092] In the evaluation of the catalytic activity of the oxygen reduction reaction of the catalyst, both electrochemical polarization and concentration polarization affect its performance. As the potential decreases, the electrochemical kinetics will accelerate and the amount of oxygen required will also increase. When the potential is lower than a certain potential (in an acidic medium, this potential is generally around 0.6V), the concentration of oxygen on the electrode surface drops to 0, achieving complete concentration polarization, and the diffusion current reaches the limiting current density. Usually when studying the catalytic performance of the oxygen reduction reaction of the catalyst, the potential at which the current density is half of the limiting current density (i.e., the half-wave potential) is used for characterization and comparison. The higher the half-wave potential, the higher the catalytic activity of the catalyst in the oxygen reduction reaction.
[0093] As can be seen from the figure, the half-wave potential of the Pt2CoLa / C ordered alloy material of Example 1 is 924mV, which is significantly higher than the Pt / C, PtCo / C and Pt5La / C catalysts provided in Comparative Examples 1-3 (respectively: 842mV, 886mV and 905mV). This shows that the introduction of rare earth metals effectively improves the catalytic activity of the catalyst for oxygen reduction reaction. This may be due to the introduction of rare earth metals, which further regulates the electronic structure of platinum and modifies the formation of a denser platinum layer, so that the adsorption energy of oxygen intermediates tends to the optimal value, thereby improving the intrinsic catalytic ability of platinum.
[0094] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A carbon-supported ternary metal ordered alloy nanomaterial, characterized in that: It includes a carbon carrier and ternary metal ordered alloy nanoparticles loaded on the surface or in the pore structure of the carbon carrier; The ternary metal ordered alloy nanoparticles include noble metals, transition metals and rare earth metals, and the three metal atoms are arranged in order.
2. The carbon-supported ternary metal ordered alloy nanomaterial according to claim 1, characterized in that: The particle size of the ternary metal ordered alloy nanoparticles is 1-50 nm; The ternary metal ordered alloy nanoparticles account for 0.1-70% of the total mass of the nanomaterial.
3. The carbon-supported ternary metal ordered alloy nanomaterial according to claim 1, characterized in that: The ratio of the molar number of the noble metal to the sum of the molar numbers of the transition metal and the rare earth metal is selected from one of 1:1, 3:1 and 1:3; The ratio of the molar number of the rare earth metal to the molar number of the transition metal is (0.01-1):
1.
4. The carbon-supported ternary metal ordered alloy nanomaterial according to claim 1, characterized in that: The carbon carrier comprises one of a natural carbon material, an artificial carbon material or a derived carbon material; The noble metal includes one or more of platinum, palladium, ruthenium, iridium, gold, rhodium, osmium or silver; The transition metal includes one or more of iron, cobalt, nickel, copper, zinc, manganese, molybdenum, tungsten, chromium, tin, lead or bismuth; The rare earth metal includes one or more of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, scandium and yttrium.
5. A method for preparing the carbon-supported ternary metal ordered alloy nanomaterial according to any one of claims 1 to 4, characterized in that: The following steps are involved: The carbon carrier, the noble metal precursor, the transition metal salt precursor, the rare earth metal salt precursor and the nitrogen-containing precursor are uniformly mixed and then calcined to obtain the carbon-supported ternary metal ordered alloy nanomaterial.
6. The method for preparing a carbon-supported ternary metal ordered alloy nanomaterial according to claim 5, characterized in that: The noble metal precursor includes one or more of noble metal acid, chloride salt or nitrate salt; The transition metal salt precursor includes one or more of nitrate, chloride, acetate or sulfate; The rare earth metal salt precursor includes one or more of nitrate, chloride, acetate or sulfate.
7. The method for preparing a carbon-supported ternary metal ordered alloy nanomaterial according to claim 5, characterized in that: The nitrogen-containing precursor includes one or more of polypyrrole, polyaniline, polythiophene, polydopamine, pyrrole, aniline, pyridine, polypyridine, ethylenediamine, triethylenetetramine, porphyrin, phthalocyanine, o-phenanthroline, imidazole, dopamine, thiophene, cyanamide, dicyandiamide, urea or melamine.
8. The method for preparing a carbon-supported ternary metal ordered alloy nanomaterial according to claim 5, characterized in that: The specific method of mixing includes one or more of grinding mixing, impregnation, ultrasonic mixing and rotary evaporation; The solvents used in the immersion method, ultrasonic mixing method and rotary evaporation method include one or more of water, ethanol, methanol, acetone, ethylene glycol or isopropanol.
9. The method for preparing a carbon-supported ternary metal ordered alloy nanomaterial according to claim 5, characterized in that: The calcination temperature is 500-1200°C, and the calcination time is 0.5-48h; The calcination is carried out in a specific atmosphere, which includes one of argon, nitrogen, helium, hydrogen-nitrogen mixed gas, hydrogen-argon mixed gas, hydrogen-helium mixed gas, carbon monoxide-nitrogen mixed gas, carbon monoxide-argon mixed gas, carbon monoxide-helium mixed gas, hydrogen or carbon monoxide, and the volume concentration of hydrogen or carbon monoxide in the mixed gas is 0.1-30%.
10. An application of the carbon-supported ternary metal ordered alloy nanomaterial according to any one of claims 1 to 4, characterized in that: The carbon-supported ternary metal ordered alloy nanomaterial is used to catalyze one or more of oxygen reduction reaction, hydrogen oxidation reaction, hydrogen evolution reaction or alcohol oxidation reaction.
Citation Information
Cited By
Preparation method of carbon-loaded noble metal-rare earth metal alloy nano composite material
CN121288813A